SOIL PHYSICAL QUALITY INDICES AND GROWTH OF JUVELINE TUNG BIOENERGY OIL TREE AS AFFECTED BY COVER CROP INTERCROPPING AND ADDITIONAL POULTRY MANURE - Awe, Gabriel Oladele; Reichert, José Miguel; Giacomini, Sandro José (REVISTA DE AGRICULTURA, 2022)
This study aimed to evaluate the impacts of cover crop intercropping and poultry manure on soil physical quality indices and tung growth in a tung-based agroforestry system. Materials and Methods: The two-year experiment was conducted during the winter and summer periods of 2012/2013 and 2013/2014 growing seasons in southern Brazil, in randomized complete block design and four replications. During the winter periods, treatments consisted of tung + crambe with or without poultry manure, tung + oats/vetch mixture, and sole tung while during the summer periods, treatments were: tung + sunflower/soybean in rotation with or without poultry manure, tung + peanut, and sole tung. Intercropped cover crops increased soil organic carbon, reduced bulk density and relative field capacity, increased available water, saturated hydraulic conductivity, air capacity, ratio air capacity/total porosity, and total nitrogen of the surface layer of the tung-based agroforestry system at the end of the two growing seasons. The soil quality index of the surface layer changed from low to average in tung plots with cover crops and followed the order: Tung+Crambe/Sunflower/Soybean ≈ Tung+Oat/Vetch/Peanut > sole tung. Poultry manure enhanced further the physical quality status of the tung field. The unprotected tung soil (sole tung) of the tung-based agroforestry system is degrading, thus conservation strategies including those evaluated in this study are advocated for securing the growing environment of juveline tree crops as well as achieving their production potentials.